Human Multilineage-differentiating Stress-Enduring Cells Exert Pleiotropic Effects to Ameliorate Acute Lung Ischemia–Reperfusion Injury in a Rat Model - Yabuki, Hiroshi; Wakao, Shohei; Kushida, Yoshihiro; Dezawa, Mari; Okada, Yoshinori (Cell transplantation, 2018)
Posttransplantation lung ischemia–reperfusion (IR) injuries affect both patient survival and graft function. In this study, we evaluated the protective effects of infused human multilineage-differentiating stress-enduring (Muse) cells, a novel, easily harvested type of nontumorigenic endogenous reparative stem cell, against acute IR lung injury in a rat model. After a 2-h warm IR injury induction in a left rat lung, human Muse cells, human mesenchymal stem cells (MSCs), and vehicle were injected via the left pulmonary artery after reperfusion. Functionality, histological findings, and protein expression were subsequently assessed in the injured lung. In vitro, we also compared human Muse cells with human MSCs in terms of migration abilities and the secretory properties of protective substances. The arterial oxygen partial pressure to fractional inspired oxygen ratio, alveolar-arterial oxygen gradient, left lung compliance, and histological injury score on hematoxylin–eosin sections were significantly better in the Muse group relative to the MSC and vehicle groups. Compared to MSCs, human Muse cells homed more efficiently to the injured lung, where they suppressed the apoptosis and stimulated proliferation of host alveolar cells. Human Muse cells also migrated to serum from lung-injured model rats and produced beneficial substances (keratinocyte growth factor [KGF], hepatocyte growth factor, angiopoietin-1, and prostaglandin E2) in vitro. Western blot of lung tissue confirmed high expression of KGF and their target molecules (interleukin-6, protein kinase B, and B-cell lymphoma-2) in the Muse group. Thus, Muse cells efficiently ameliorated lung IR injury via pleiotropic effects in a rat model. These findings support further investigation on the use of human Muse cells for lung IR injury.